Microgrids and active distribution networks - Chowdhury, S. (Sunetra); Chowdhury, S. P.; Crossley, P. (London, United Kingdom The Institution of Engineering and Technology, 2009)
A companion to embedded generation (IET, 2000), this book is a timely publication for an evolving industry. Renewable energy, ancillary services and deregulation of the power industry are changing electricity delivery networks. Microgrids, smartgrids and active distribution networks require a sound understanding of the basic concepts, generation technologies, impacts, operation, control and management, economic viability and market participation involved in grid integration. Practicing engineers in utilities and industry, researchers and students will appreciate this lucid description of the technologies that will enable future electricity systems.
Also available in print version.
Electronic reproduction.
Keywords: Distributed generation of electric power; Deregulation; Electric power distribution; Electric power systems; Electric utilities; Renewable energy sources; Electronic books